The Development of Creative Economy : Case Study of Jodipan Colorful Village In Malang - Maesa Rani; Dwi Wulandari (Economics Development Analysis Journal, 2018)
The purpose of this study aim at understanding the development of creative economy in order to increase economic welfare of local community. The establishment of Jodipan Colorful Village which based on creative economy is a way to control the amount of slum area and was able to increase the economic welfare of society as expected. The qualitative descriptive approach aimed at get deep pictures about the researched situation and progress. Based on the results, we can conclude the creative economy development in a form of tourism village has been improving the economic welfare of local community in Jodipan Colorful Village. The economic welfare improvement is shown by the increase of job opportunities after Jodipan Colorful Village is established as tourism village in Malang, Indonesia. Another impact of established Jodipan Colorful Village enables the local citizens become more productive, have their own income, and the environment is well maintained.